2017
DOI: 10.1002/gcc.22458
|View full text |Cite
|
Sign up to set email alerts
|

The enigmatic oncogene and tumor suppressor‐like properties of RAD54B: Insights into genome instability and cancer

Abstract: One of the major challenges to the cell is to ensure genome stability, which can be compromised through endogenous errors or exogenous DNA damaging agents, such as ionizing radiation or common chemotherapeutic agents. To maintain genome stability the cell has a multifaceted line of defense, including cell cycle checkpoints and DNA damage repair pathways. RAD54B is involved in many of these pathways and thus exhibits a role in maintaining and repairing genome stability following DNA damage. RAD54B is involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 89 publications
(182 reference statements)
0
12
0
Order By: Relevance
“…A fundamental assumption of gene copy number alterations is that they induce corresponding changes in gene expression and that SKP1 copy number gains and losses are expected to underlie aberrant SCF complex activity leading to cellular dysfunction, genome instability and potentially tumorigenesis. Indeed, strong positive correlations exist between copy number changes and mRNA expression for all 12 cancer types investigated ( Figure 3 ), and while the copy number alterations detailed above suggest SKP1 may encode both oncogene-like or tumor suppressor-like functions, these seemingly opposing activities are not specific to SKP1 and have been reported for other genes including TP53 ( Lane, 1984 ; Jenkins et al, 1985 ; Finlay et al, 1989 ), USP22 ( Jeusset and McManus, 2017 ), and RAD54B ( McAndrew and McManus, 2017 ).…”
Section: Skp1 Expression Is Frequently Altered In Human Cancersmentioning
confidence: 71%
“…A fundamental assumption of gene copy number alterations is that they induce corresponding changes in gene expression and that SKP1 copy number gains and losses are expected to underlie aberrant SCF complex activity leading to cellular dysfunction, genome instability and potentially tumorigenesis. Indeed, strong positive correlations exist between copy number changes and mRNA expression for all 12 cancer types investigated ( Figure 3 ), and while the copy number alterations detailed above suggest SKP1 may encode both oncogene-like or tumor suppressor-like functions, these seemingly opposing activities are not specific to SKP1 and have been reported for other genes including TP53 ( Lane, 1984 ; Jenkins et al, 1985 ; Finlay et al, 1989 ), USP22 ( Jeusset and McManus, 2017 ), and RAD54B ( McAndrew and McManus, 2017 ).…”
Section: Skp1 Expression Is Frequently Altered In Human Cancersmentioning
confidence: 71%
“…Further studies clarified that RAD54B belongs to SWI2/SNF2 helicase superfamily and is involves in modulating the DNA damage checkpoint response [10] and homologous recombination repair (HRR) pathway [11] . Accordingly, sequencing assay uncovered that multiple human cancers are implicated in alterations of RAD54B such as gene amplification, homozygous deletion and non-synonymous single nucleotide polymorphism [12] , [13] , [14] , [15] , [16] , [17] . Of note, wang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Since RAD54B ensures faithful and accurate repair of DNA damage, its overexpression and downregulation would perturb genomic instability which could confer oncogenic properties. 20 Previous data has shown that suppression of RAD54B could block proliferation and promote apoptosis of liver and lung cancer cells. 21 , 22 In addition, RAD54B could remarkably facilitate cancer progression in breast cancer.…”
Section: Discussionmentioning
confidence: 99%